Education of people with autism spectrum disorders: state of knowledge in dissertations and theses in the Southern and Southeastern regions of Brazil (2008-2016) - Wuo, Andrea Soares (Saúde e Sociedade, 2019)
Current special education policies seek to ensure people with disabilities, global developmental delay and high skills/giftedness access, permanence, participation and learning in the regular school. Among students considered to be “target audience of special education” are those with the socalled “autism spectrum disorder”. This study aimed to analyze the state of knowledge about autism spectrum disorders, based on theses and dissertations produced in the southern and southeastern regions of Brazil from 2008 to 2016. The analysis showed autism is defined using different approaches, most of them being guided by explanations in the medical field, linked to a notion of psychological and social deficit and impairment. Studies guided by a critical perspective, which values the educational, social and historical conditions of the subject’s constitution were also observed. One concludes that, although knowledge about autism is still in the domain of medical areas, the emergence of investigations in the scope of school inclusion allows the construction of ways of thinking the schooling process that surpasses exclusively medical models of looking at the difference.